Peran Harga sebagai Variabel Mediasi antara Personal Branding Kualitas Layanan terhadap Keputusan Pembelian Platform TikTok - Anisa Nur Sholikah; Siti Musarofah; Amanatul Khoiriyah; Muhammad Sulton (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to examine the influence of personal branding and service quality on purchase decisions, with price serving as a mediating variable on the TikTok Shop platform. The increasing trend of online shopping activities has encouraged businesses to strengthen their digital marketing strategies, including enhancing personal branding and improving service quality. This research applies a quantitative approach using a survey method. Data were collected from 91 students of Institut Teknologi dan Bisnis Ahmad Dahlan Lamongan who had made purchases through TikTok Shop using a Likert-scale questionnaire. The data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) technique with the assistance of SmartPLS software. The findings indicate that personal branding and price have a significant effect on purchase decisions. Meanwhile, service quality does not have a direct effect on purchase decisions. However, personal branding and service quality significantly influence price. Furthermore, price is able to mediate the relationship between personal branding and service quality and purchase decisions. These findings emphasize that price plays a strategic role in shaping consumer purchase decisions on digital platforms.